Engineered production of cancer targeting peptide (CTP)-containing C-1027 in Streptomyces globisporus and biological evaluation. Issue 17 (1st September 2016) - Li, Wenli; Li, Xiuling; Huang, Tingting; Teng, Qihui; Crnovcic, Ivana; Rader, Christoph; Shen, Ben
Graphical abstract: Abstract: Conjugation of cancer targeting peptides (CTPs) with small molecular therapeutics has emerged as a promising strategy to deliver potent (but typically nonspecific) cytotoxic agents selectively to cancer cells. Here we report the engineered production of a CTP (NGR)-containing C-1027 and evaluation of its activity against selected cancer cell lines. C-1027 is an enediyne chromoprotein produced by Streptomyces globisporus, consisting of an apo-protein (CagA) and an enediyne chromophore (C-1027). NGR is a CTP that targets CD13 in tumor vasculature. S. globisporus SB1026, a recombinant strain engineered to encode CagA with the NGR sequence fused at its C-terminus, directly produces the NGR-containing C-1027 that is equally active as the native C-1027. Our results demonstrate the feasibility to produce CTP-containing enediyne chromoproteins by metabolic pathway engineering and microbial fermentation and will inspire efforts to engineer other CTP-containing drug binding proteins for targeted delivery.